The Effect of TOEFL Preparation Course on EFL Undergraduate Students’ TOEFL Scores - Nita Kaniadewi; Dinda Ismu Asyifa (Linguistic, English Education and Art (LEEA) Journal, 2022)
TOEFL is important to measure one’s English proficiency, especially for higher education students. This test is frequently used for many purposes such as applying for a job and scholarship. Several universities in Indonesia use TOEFL as a graduation requirement, which means the students must take the TOEFL test before graduation. In mastering TOEFL, some students got difficulties because of some reasons. Therefore, the TOEFL preparation program was needed for students to increase their TOEFL scores. This study aimed to find out the effectiveness of the TOEFL preparation course on students’ TOEFL scores. This research was quantitative experimental research. There were 80 EFL students from various study programs in the Faculty of Teacher Training and Education, University of Muhammadiyah Prof. Dr. HAMKA who participated in this study. Before conducting the preparation program, the students took a TOEFL pre-test. After that, they took a TOEFL preparation class for seven meetings. The TOEFL post-test was used to see participants’ different scores after the preparation course was held and the result revealed that the students’ scores increased from the previous pre-test. Thus, TOEFL preparation classes are significant in improving students’ TOEFL scores and therefore recommended for students who want to take the TOEFL test. Keywords: TOEFL, TOEFL Preparation, TOEFL Score, EFL Students